2015
DOI: 10.1155/2015/751530
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic System Activation Mediates Changes in Cardiovascular and Psychomotoric Reactions in Young Individuals after Red Bull©Energy Drink Consumption

Abstract: Objectives. To assess the effect of Red Bull© on (1) blood glucose and catecholamine levels, (2) cardiovascular and respiratory function changes before, during, and after exercise, (3) reaction time, (4) cognitive functions, and (5) response to mental stress test and emotions in young healthy individuals (N=38). Methods. Heart rate (HR) and arterial blood pressure (ABP), blood glucose, adrenaline, and noradrenalin plasma levels were measured before and after Red Bull© intake. Participants were subjected to 4 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“… 10 Cavka et al have recently shown that energy drinks raise the plasma levels of adrenaline and noradrenaline significantly above the preconsumption level within a period of 60 minutes. 2 The dual effects on QTc and HRV seen in the present study probably reflect a tendency towards autonomic imbalance in obese subject’s that are comparable to those documented by other researchers. 23 , 25 , 31 , 32 A combination of reduced HRV along with prolongation of QTc has also been demonstrated in patients with untreated essential hypertension who do not exhibit cardiac hypertensive disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“… 10 Cavka et al have recently shown that energy drinks raise the plasma levels of adrenaline and noradrenaline significantly above the preconsumption level within a period of 60 minutes. 2 The dual effects on QTc and HRV seen in the present study probably reflect a tendency towards autonomic imbalance in obese subject’s that are comparable to those documented by other researchers. 23 , 25 , 31 , 32 A combination of reduced HRV along with prolongation of QTc has also been demonstrated in patients with untreated essential hypertension who do not exhibit cardiac hypertensive disease.…”
Section: Discussionsupporting
confidence: 90%
“…Energy drinks are beverages consumed for an extra boost in vitality, promoting wakefulness, maintaining alertness and providing cognitive and mood enhancement. 1 , 2 With a reported 34.5 million consumers worldwide, marketing efforts are particularly aimed at college/university students. 3 A study at State University in the Central Atlantic region of the United States reported that over half of the college students drink at least one energy drink per month.…”
mentioning
confidence: 99%
“…Recently, Cavka and co-workers were able to demonstrate an increased respiratory rate and flow rate, respectively, at rest and during moderate exercise after ingestion of half a litre of Red Bull in 38 college students. These researchers showed an activation of the sympathetic nervous system and hypothesized a notable dilation of bronchioles [33]. Recent data from Spanish colleagues showed an increased cycling performance in ambient air as well as enhanced muscle oxygen saturation assessed at the thigh at moderate workloads (30-60% of VO 2max ) after caffeine intake (3 mg/kg).…”
Section: Discussionmentioning
confidence: 96%
“…Also, in terms of the effect of ED on the HR, non-homogeneous results were obtained (mostly with no effect or increase in the HR) 22,28 , but there was also a study published, showing how ED influenced the reduction of the HR 39 . It has been shown that a higher dose of RB ® (355 ml) affects the increase in systolic and diastolic arterial pressure and the increase in the HR 40 , as well as that RB ® at a dose of 500 ml affects the increase in the activity of the sympathetic nervous system 41 . The previously said can be explained by the effect of EDs on the increase in norepinephrine levels 42 , which increases the HR and blood pressure, triggers the release of glucose from energy stores and increases blood flow to skeletal muscles 16 .…”
Section: Discussionmentioning
confidence: 99%